An improved algorithm for evaluation of the product of an exponential function with an error function complement - Dewhurst, R.J.; Shan, Q. (Microprocessing and microprogramming, 1996)
Some mathematical CAD packages are inadequate in computing the composite functions involving the product of an exponential function and an error function complement. These functions arise in physical applications, such as problems in diffusion. Their importance warrants a composite treatment. If their component factors are computed individually, discontinuities in the evaluations arises, as shown in some CAD packages. An improved algorithm is presented which overcomes this deficiency, and provides a fast evaluation. Such evaluation is successful even using floating point numbers with single precision. The potential for numerical overflow associated with large arguments has been overcome.